1953
DOI: 10.2136/sssaj1953.03615995001700030021x
|View full text |Cite
|
Sign up to set email alerts
|

Nine Essential Amino Acids in the Protein of Wheat and Barley Grown on Sulfur‐Deficient Soil

Abstract: The investigation was undertaken to study the possible effects of fertilizers and cropping systems on the quality of grain protein as measured by total content and proportions of nine essential amino acids. Amino acid determinations were made on acid hydrolysates of ground grain using a microbiological assay method. All grains were grown on sulfur‐deficient gray wooded soil. Most of the samples were from plots originally laid out in 1930 for long term tests to compare the effects on crop yields of various fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1958
1958
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…25,26,27,28,3 Current recommended fertilization practices in these soils call for N, P and S application for grains and P and S application for legumes. In addition to yield responses, adequate N, P and S fertilization resulted in higher protein in grains especially in the five-year rotation, 29,1 and added P and S resulted in a higher nutritional feed quality for forages. 2,33 Although McAllister 18 recommended addition of potassium (K) fertilizers in addition to N and P fertilizers, long-term crop responses to added K at Breton have been small.…”
Section: Responses To Nitrogen Phosphorus Sulfur and Potassium Fertmentioning
confidence: 99%
“…25,26,27,28,3 Current recommended fertilization practices in these soils call for N, P and S application for grains and P and S application for legumes. In addition to yield responses, adequate N, P and S fertilization resulted in higher protein in grains especially in the five-year rotation, 29,1 and added P and S resulted in a higher nutritional feed quality for forages. 2,33 Although McAllister 18 recommended addition of potassium (K) fertilizers in addition to N and P fertilizers, long-term crop responses to added K at Breton have been small.…”
Section: Responses To Nitrogen Phosphorus Sulfur and Potassium Fertmentioning
confidence: 99%
“…All except Proctor are 6-row barley, whereas the varieties grown in New Zealand are usually 2-row barleys. McElroy et al (1949) and Renner, Bentley, and McElroy (1953) found no significant difference between the amino acid concentrations in barleys harvested in different seasons.…”
Section: Introductionmentioning
confidence: 87%
“…This result is at variance with the findings of McElroy et at. (1949) and Renner et al (1953), who found no significant effect of season on barley amino acid com" position.…”
Section: (Iii) Seasonal Effectmentioning
confidence: 94%
“…Later, Wyatt (1945) also reported the response of alfalfa and clover to applied S. The effects of rotation on crop response to fertilizer were first emphasized in the publication by Wyatt et al (1939) and later in Wyatt (1945) and Juma et al (1997a), where it was reported that wheat response to added N and P was much greater following clover than following wheat or fallow. Later, S cycling and response of cereals and forages to applied S were investigated more extensively (Cormack et al 1951;Renner et al 1953;Bentley et al 1955;Bentley et al 1956;Bentley et al 1960;Pawluk and Bentley 1964). Other investigations focussed on rotation effects on speciation and cycling of N (Khan 1971;Monreal and McGill 1985;Rutherford and Juma 1989;Wani et al 1991Wani et al , 1994Juma 1995), P (Odynsky 1936;McKenzie et al 1992;Morel et al 1994), and C (Juma et al 1997a(Juma et al , 1997bCampbell et al 1997;Janzen et al 1998;Grant et al 2001;Izaurralde et al 2001aIzaurralde et al , 2001bPaul et al 2004;Izaurralde et al 2006).…”
Section: Introductionmentioning
confidence: 99%